Dehydration and performance on clinical concussion measures in collegiate wrestlers - Weber, A. F.; Mihalik, J. P.; Register-Mihalik, J. K.; Mays, S.; Prentice, W. E.; Guskiewicz, K. M. (Journal of Athletic Training, 2013)
Context: The effects of dehydration induced by wrestling-related weight-cutting tactics on clinical concussion outcomes, such as neurocognitive function, balance performance, and symptoms, have not been adequately studied. Objective: To evaluate the effects of dehydration on the outcome of clinical concussion measures in National Collegiate Athletic Association Division I collegiate wrestlers. Design: Repeated-measures design. Setting: Clinical research laboratory. Patients or Other Participants: Thirty-two Division I healthy collegiate male wrestlers (age = 20.0 ± 1.4 years; height = 175.0 ± 7.5 cm; baseline mass = 79.2 ± 12.6 kg). Intervention(s): Participants completed preseason concussion baseline testing in early September. Weight and urine samples were also collected at this time. All participants reported to prewrestling practice and postwrestling practice for the same test battery and protocol in mid-October. They had begun practicing weight-cutting tactics a day before prepractice and postpractice testing. Differences between these measures permitted us to evaluate how dehydration and weight-cutting tactics affected concussion measures. Main Outcome Measures: Sport Concussion Assessment Tool 2 (SCAT2), Balance Error Scoring System, Graded Symptom Checklist, and Simple Reaction Time scores. The Simple Reaction Time was measured using the Automated Neuropsychological Assessment Metrics. Results: The SCAT2 measurements were lower at prepractice (P = .002) and postpractice (P < .001) when compared with baseline. The BESS error scores were higher at postpractice when compared with baseline (P = .015). The GSC severity scores were higher at prepractice (P = .011) and postpractice (P < .001) than at baseline and at postpractice when than at prepractice (P = .003). The number of Graded Symptom Checklist symptoms reported was also higher at prepractice (P = .036) and postpractice (P < .001) when compared with baseline, and at postpractice when compared with prepractice (P = .003). Conclusions: Our results suggest that it is important for wrestlers to be evaluated in a euhydrated state to ensure that dehydration is not influencing the outcome of the clinical measures.